Essential Workers and Transit Ridership Retention During COVID-19 Shocks in the Toronto Region - Sana Riaz; Christopher Higgins; Steven Farber (Findings)
This paper investigates the relationship between ridership loss and socioeconomic characteristics across 333 transit surface routes (buses and streetcars). Using beta regression, we model ridership loss as a function of Census-derived variables including income, car as main mode of travel, visible minority, housing burden, and the concentration of essential workers. We find that routes serving areas with higher percentages of essential workers retained more riders, while routes in car-dependent areas saw greater losses. These results reinforce the idea that essential workers---disproportionately lower-income and racialized---are "essential riders" for whom transit remains an essential service, referred to as "dual essentiality".